Kinship and diplomacy in sixteenth-century Scotland: the earl of Northumberland's Scottish captivity in its domestic and international context, 1569–72. Issue 236 (13th April 2014) - Blakeway, Amy
Abstract: Following the English northern rebellion of 1569, several high profile rebels crossed the border to Scotland. One of their number, the earl of Northumberland, was captured and incarcerated by the Scots until 1572. This article explores the hitherto neglected impact of Northumberland's presence in Scotland upon Scottish domestic politics, demonstrating the extent to which Anglo-Scottish diplomatic negotiations were contingent upon the satisfaction of a range of domestic Scottish interests. Paramount among these was the need felt by leading Scots such as John Erskine, earl of Mar and then regent, and James Douglas, earl of Morton, to satisfy their kin and dependants.